Characterization of the bond quality of adhesive plates utilizing zero-group-velocity Lamb waves measured by a laser ultrasonics technique - Hideo CHO (The Japan Society of Mechanical Engineers, 2014)
The bonding quality of an adhesive component was estimated using the frequency of zero-group-velocity (ZGV) Lamb waves, which can be generated and detected with a laser ultrasonic technique. Two distinct peaks corresponding to ZGV Lamb waves in the amplitude spectrum were obtained for well- and weak-bonded adhesive plate samples. The frequency difference between the measured low frequency mode and the calculated frequency, which can be obtained by assuming a continuous stress and strain at a bonding interface, linearly increased with shear strength, as obtained by the shear-tensile test. The frequency of ZGV Lamb waves was also calculated with reduced shear modulus of the bonding layer to express a weak bonding, and the change in the calculated frequency in low frequency ZGV Lamb waves showed a similar tendency to that in measured one.